PSYCONALYSIS LITERATURE CRITICS: MAHDI CHARACTERS IN JENNY & MAHDI MULIADI GF’S SHORT STORY - Suprihatien, Suprihatien; Damayanti, Rini (Universitas Hamzanwadi, 2020)
In general, this study aims to describe the character and inner conflict of Mahdi's character in the Jenny & Mahdi short story by Muliadi GF. Based on the problem above, this study aims as follows to describe the character of the characters in the Jenny & Mahdi short story by Muliadi GF; and describe the inner conflict with the short story character Jenny & Mahdi by Muliadi GF. The method used is the method of literary criticism in the form of text analysis (literary works) because only with analysis of any literary work can the meaning be explained. The characters of Mahdi in this short story include: a person who never gives up, a person who is closed and doesn't talk much, and anger and curses. The inner conflict of Mahdi's character in this short story covers inner conflict because of his closed attitude and solitude and inner conflict due to obsession.Keywords: character; conflict; critic